2018
DOI: 10.3233/wor-182753
|View full text |Cite
|
Sign up to set email alerts
|

Worker acceptability of the Pennington Pedal Desk™ occupational workstation alternative

Abstract: Participants rated the Pennington Pedal Desk™ workstation positively and indicated potential for extended daily use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…9 Recent attempts to improve workplace activity include sit-stand desks, 10 treadmill desks, 11 and portable pedal devices. 12 Use of these devices could be promoted by emphasizing their health benefits and reducing sedentary time in the workplace. 9,13,14 The use of portable pedal exercise machines has been studied to help improve activity by increasing energy expenditure.…”
mentioning
confidence: 99%
“…9 Recent attempts to improve workplace activity include sit-stand desks, 10 treadmill desks, 11 and portable pedal devices. 12 Use of these devices could be promoted by emphasizing their health benefits and reducing sedentary time in the workplace. 9,13,14 The use of portable pedal exercise machines has been studied to help improve activity by increasing energy expenditure.…”
mentioning
confidence: 99%
“…They found a greater appreciation of the pedal desk over standing for its effective, useful, functional, convenient, and comfortable dimensions. During a standard 8-h working day, 97.6% of subjects reported that their typing proficiency could not be influenced by a 4-h employment of the pedal desk ( 89 ). Moreover, besides working productivity, the rates of compliance deserve attention.…”
Section: Strategies To Increase Neat At Workmentioning
confidence: 99%
“…The uses of treadmill and cycling desks, as well as micro-breaks, have been recommended as strategies to reduce the time spent sitting at work [ 27 , 28 ]. Carr et al [ 29 , 30 ] investigated the practicality and feasibility of a portable pedaling exercise equipment on middle-aged participants, primarily female, who worked in sedentary environments and randomized them into an intervention and a controlled group.…”
Section: Introductionmentioning
confidence: 99%